"Endourological closure of a malformative vascular source of bleeding using the VortX 0.018" coil®". Issue 4 (November 2021) - De Gobbi, Alberto; Barbisan, Davide; Ciaccia, Matteo; Cova, Giandavide; Farneti, Fabrizio; Maccatrozzo, Luigino; Mangano, Mario Salvatore
Aims: Renal vascular malformations, congenital or acquired, are sometimes challenging for urologists and interventional radiologists to resolve. Arterovenous fistulas and pseudoaneuryms are usually embolized by interventional radiologists, with a low rate of complications. We propose a new endourological/interventional radiology technique to treat a source of arterovenous bleeding coming from a renal calyx in a minimally invasive way. Methods: A combined endourological and interventional radiology procedure is described, using a Flexible Fiberoptic Ureteroscopes to undertake a retrograde intrarenal surgery (RIRS) to identify the source of bleeding; subsequently the VortX Coil® is inserted through a microcatheter to stop the bleeding and the correct position of the VortX coil is evaluated. Furthermore, we made a literature research on Pubmed and Medline to look for similar procedures. Results: In case of a renal bleeding that could not be treated by endovascular way, a combined urological and interventional radiology procedure can be undertaken. We did not find similar endourological and interventional radiology procedure on Pubmed and Medline, so this is the first tecnique of endourological closure of a bleeding point using a coil. Conclusion: From our experience this could be a mininvasive technique to solve renal bleedings coming from a calyx that are not found by endovascular approach. Indeed, in our knowledge, the technique here described is the first that provides the use of an endovascular coil by endourological way in renal vascular malformations.